Oral History Program Interview: Dorothy Louise Price Rose - Rose, Dorothy Louise Price
Rose's poems about her Dust Bowl experience add an interesting perspective to the Odyssey Project. Born in 1921 in Lamar, Arkansas, she recounts her childhood on the farm and at Church events. Her family moved to California in 1936 and eventually to the valley during World War II. Her family begrudgingly accepted relief through the WPA and food stamps. Her father was part of a union and paid dues. "Okie" was a derogatory word but is currently based on discrimination. The Grapes of Wrath captured the migrants' plight, yet it made the people look very poorly.